Sosialisasi Etika Bisnis dan Entrepreneur UMKM – Setu Babakan Srengseng Sawah Jagakarsa Jakarta Selatan - Sundara, Dadan; Laksono, Rudi; Gultom, Junias Robert (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
The Covid-19 pandemic provides impact drops visitors at tourist Setu Babakan that affect the decline in the turnover of sales for the SMEs. They need new strategic to change conventional marketing to the digital marketing should be done by SMEs to recover turnover of sales. On the other hand, the background education of SMEs is majority educated school middle so application of business ethics has not fully implemented by SMEs This program aims to add to management knowledge, especially regarding business ethics for SMEs and entrepreneurial learning in marketing online / digital marketing. The results of this program showing a positive impact, namely increasing knowledge by MSMEs regarding business ethics and entrepreneurs to use online marketing / digital marketing so that it can be implemented in increasing their sales Keyword: Business Ethics, Entrepreneur, MSMEs, Digital Marketing